The acute effect of verbal instructions on performance and landing when dropping from different heights: the ground reaction force-time profile of drop vertical jumps in female volleyball athletes - La Greca, Stefano; Antonacci, Gaetano; Marinelli, Stefano; Cifelli, Pierangelo; Di Giminiani, Riccardo (Frontiers in Sports and Active Living, 2024)
Introduction The drop vertical jump (DVJ) is extensively utilized for conditioning and evaluating physical performance, as well as reducing the likelihood of injury by enhancing joint stability through the coactivation of muscles acting on the joint. The execution of DVJ can be controlled by verbal instructions and evaluated by the vertical ground reaction force (vGRF)-time profile. Methods Our hypothesis was that varying verbal instructions could have an impact on the DVJ's parameter, thereby optimizing vertical performance and minimizing the impact during landing in young female volleyball players. Sixteen female volleyball players volunteered to participate in this study (age: 21.3 ± 2.6 years; stature: 1.66 ± 0.1 m; body mass: 62.0 ± 8.1 kg and BMI: 22.2 ± 1.8). They executed DVJs following verbal instructions ranging from “jump as high as possible” (1A), “jump as quickly as possible” (2A), “jump as high as possible and during the landing attempt to dampen the impact at ground contact” (1B), and “jump as high as quickly as possible and during the landing attempt to damp the impact at ground contact” (2B). The reactive strength index (RSI), vGRF (1st and 2nd peaks), and flight time (FT) were evaluated. Results The verbal instructions 1A improved the FT and the first peak of the vGRF (P < 0.05), whereas 2A the RSI (P < 0.05). On the contrary, “the damping” required in the 1B, and 2B verbal instruction reduced the 2nd peak of vGRF (P < 0.05), without altering the task required during the jump (P < 0.05). Discussion The instructions provided for the final landing (the second peak of vGRF) have the potential to enhance safety by reducing the peak of vGRF without affecting the performance required during the jump. When designing DVJ training, coaches or kinesiologists must consider the use of verbal instructions to induce specific adaptation over time. Clinical relevance The present study supports the use of specific verbal instructions to reduce impact forces in landing and injury risk.